A distinctive distribution of hypoxia‐inducible factor‐1α in cultured renal tubular cells with hypoperfusion simulated by coverslip placement. Issue 1 (28th December 2020) - Honda, Tomoko; Hirakawa, Yosuke; Mizukami, Kiichi; Yoshihara, Toshitada; Tanaka, Tetsuhiro; Tobita, Seiji; Nangaku, Masaomi
Abstract: Chronic hypoxia in the renal tubulointerstitium plays a key role in the progression of chronic kidney disease (CKD). It is therefore important to investigate tubular hypoxia and the activity of hypoxia‐inducible factor (HIF)‐1α in response to hypoxia. Rarefaction of the peritubular capillary causes hypoperfusion in CKD; however, the effect of hypoperfusion on HIFs has rarely been investigated. We induced hypoperfusion caused by coverslip placement in human kidney‐2 cells, and observed an oxygen gradient under the coverslip. Immunocytochemistry of HIF‐1α showed a doughnut‐shaped formation on the edge of a pimonidazole‐positive area, which we named the "HIF‐ring". The oxygen tension of the HIF‐ring was estimated to be between approximately 4 mmHg and 20 mmHg. This result was not compatible with those of past research showing HIF‐1α accumulation in the anoxic range with homogeneous oxygen tension. We further observed the presence of a pH gradient under a coverslip, as well as a shift of the HIF ring due to changes in the pH of the culture medium, suggesting that the HIF ring was formed by suppression of HIF‐1α related to low pH. This research demonstrated that HIF‐1α activation mimics the physiological state in cultured cells with hypoperfusion. Abstract : We examined HIF‐1α distribution in the hypoperfusion model using a coverslip and immunicytochemistry of HIF‐1α in HK‐2 cells showed a doughnut‐shaped enhancement just on the edge of the pimonidazole‐positive area, which we called the "HIF ring". We discovered that there was pH gradient as well as oxygen gradient at the coverslip edge in the hypoperfusion model, induced by coverslip placement. We proposed the possible mechanism of HIF ring formation that, despite HIF‐1α accumulation with decreasing oxygen tension, the accumulation was suppressed because of low pH within a certain distance from a coverslip edge.